A Nanostructured Si/SiOC Composite Anode with Volume‐Change‐Buffering Microstructure for Lithium‐Ion Batteries. Issue 10 (21st January 2019) - Wu, Ze; Lv, Weiqiang; Cheng, Xinqun; Gao, Jinlong; Qian, Zhengyi; Tian, Dong; Li, Ji; He, Weidong; Yang, Chunhui
Abstract: Si/SiOC composites are promising high‐capacity anode materials for lithium‐ion batteries since the SiOC matrix can effectively buffer the volumetric change of Si during cycling. However, a structure of Si nanoparticles (NPs) enwrapped by a continuous SiOC phase typically shows poor cyclic stability and low charge/discharge rate due to structure failure of bulk SiOC shells derived from carbon‐rich organosilicon. To address this issue, in this work, an Si/SiOC nanocomposite with volume‐change‐buffering microstructure, in which Si NPs are uniformly dispersed in a matrix of SiOC nanospheres, has been synthesized. Our results show that the space between Si and SiOC NPs can accommodate the large volume change of Si during cycling and facilitate infiltration of the electrolyte. The nanostructured SiOC skeleton serves as both a mechanically robust buffer to alleviate the intrinsic expansion of Si and an effective electron conductor. The Si/SiOC NP composite displays significantly increased capacity and cyclic stability compared with pure SiOC, and delivers reversible capacities of around 800 mA h −1 g −1 at a current density of 100 mA g −1 (approximately 100 % capacity retention after 100 cycles) and around 600 mA h −1 g −1 at 500 mA g −1 (capacity retention about 80 % after 500 cycles). Abstract : Expanding into the gaps : Combining Si and SiOC nanoparticles in appropriate proportions affords an electrode material with superior properties as an anode for lithium‐ion batteries. The voids between the particles accommodate the volume changes of Si during cycling (see figure).